Pengaruh Pendidikan dan Pengangguran terhadap Tingkat Kemiskinan di Kabupaten Muaro Jambi - Solmidawati; Nurdin; Sari, Yolanda (Teewan Journal Solutions, 2026)
This study aims to analyze the influence of education and unemployment on poverty levels in Muaro Jambi Regency. Education and unemployment are considered important socioeconomic factors that directly affect community welfare. The research employs a quantitative approach using secondary data obtained from the Central Bureau of Statistics (BPS) of Jambi Province and Muaro Jambi Regency. The variables used in this study include education (measured by average years of schooling), unemployment (measured by the open unemployment rate), and poverty (measured by the percentage of poor population). The analytical method applied is multiple linear regression to examine the partial and simultaneous effects of the independent variables on poverty. The results show that education has a significant negative effect on poverty, indicating that a higher level of education reduces poverty. Conversely, unemployment has a significant positive effect on poverty, implying that an increase in unemployment raises the poverty rate. Furthermore, education and unemployment simultaneously have a significant effect on poverty levels in Muaro Jambi Regency. The findings suggest that efforts to reduce poverty should focus on expanding access to education and reducing unemployment through job creation programs and skill development. These results are expected to serve as a reference for policymakers in formulating poverty alleviation strategies in Muaro Jambi Regency